2003
DOI: 10.1046/j.1600-6143.2003.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Chemokine and Chemokine Receptor Gene Induction by Ischemia, Alloantigen, and Gene Transfer in Cardiac Grafts

Abstract: Transplantation of allogeneic grafts presents several challenges to the innate and adaptive immune systems including chemokine leukocyte recruitment, activation, and effector function. We defined the chemokines and receptors induced by the transplant procedure/ischemia injury, alloantigen and gene transfer vector administration in murine cardiac grafts. E1, E3 deleted AdRSVbgal was transferred into grafts at the time of transplantation, grafts were harvested after 1-14 days, and a pathway-specific cDNA array w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…As shown in Figure 3A, the majority of chemokines and chemokine receptors analysed in this study were expressed by both MSCs and rDCs (n = 4). Interestingly, CCL2 (MCP-1), CXCL12 (SDF-1α) and CX3CL1 (fractalkine) were the only chemokine mRNAs expressed at higher levels in MSCs compared to DCs which is in agreement with a number of other studies [17], [31], [32]. For all other studied molecules, however, mRNA expression levels were between factor 10 and 1×10 5 times lower in MSCs compared to DCs.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As shown in Figure 3A, the majority of chemokines and chemokine receptors analysed in this study were expressed by both MSCs and rDCs (n = 4). Interestingly, CCL2 (MCP-1), CXCL12 (SDF-1α) and CX3CL1 (fractalkine) were the only chemokine mRNAs expressed at higher levels in MSCs compared to DCs which is in agreement with a number of other studies [17], [31], [32]. For all other studied molecules, however, mRNA expression levels were between factor 10 and 1×10 5 times lower in MSCs compared to DCs.…”
Section: Resultssupporting
confidence: 90%
“…Chen and colleagues found that multiple chemokines and chemokine receptors were up-regulated in Ad-transduced murine cardiomyocytes compared to untransduced cardiomyocytes. Furthermore, they found that Ad-transduction induced a broader panel of chemokines and receptors than that induced by either ischemia or alloantigen [17]. Similarly, Zhang and co-workers reported significantly greater expression of a number of chemokines and chemokine receptors in Ad-transduced pancreatic islet cells compared to untransduced cells [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 1 shows the time course of gene expression of the MCP-1/CCL2 and its corresponding receptor CCR2, RAN-TES/CCL5 and CCR5, and IP-10/CXCL10 and Mig/CXCL9, ligands for the CXCR3 pathways, in syngeneic and allogeneic grafts as assessed by quantitative real-time PCR. These results confirmed the very good correlation with the cDNA array results, as previously reported (12,15,16).…”
Section: Induction Of Chemokines and Chemokine Receptor Genes During supporting
confidence: 91%
“…The increased expression of the chemokine SDF-1 and its receptor, CXCR4, is another major finding of our study. Both CXCL1 and CXCL5 are among the chemokine genes noted to be highly induced in the early phase in response to ischemia reperfusion injury in animal models of cardiac transplantation (26). In earlier studies, a dual pattern of chemokine induction was reported in response to ischemiareperfusion injury: an early phase of macrophage inflammatory protein-2 and monocyte chemoattractant protein-1 production and a late phase of lymphotactin, RANTES (regulated upon activation normal T-cell expressed and secreted), and interferon-inducible protein-10 expression, which correlated with the subsequent development of cardiac allograft vasculopathy (27,28).…”
Section: Discussionmentioning
confidence: 99%